Invasive and non-invasive sampling in genetic analysis and its use in determining the fecal microbiome of barbary sheep (Ammotragus lervia), cattle, and goats in the chihuahuan desert, México - Ramírez García, Jesús Gabriel (Universidad Autónoma Chapingo, 2026)
This literature review combines a scientometric analysis and a systematic review, as well as a metagenomic microbiological study, focusing on conservation genetics and the microbial ecology of wild terrestrial mammals. The results demonstrate a rapid expansion of population genetics in recent decades and a shift toward non invasive methodologies, which have broadened taxonomic and geographic coverage while reducing animal handling. Although invasive sampling provides DNA of higher integrity, advances in quality control, amplification, and sequencing have increased the reliability of non-invasive methods. Differences in Ho, He, and Fis were moderate when considering species and markers, highlighting the importance of quality control and methodological transparency. Regional biases and challenges associated with the transition from microsatellites to SNPs were also identified. In addition, the fecal microbiome of Barbary sheep (Ammotragus lervia), cattle (Bos taurus), and goats (Capra aegagrus hircus) living in sympatry in the Santa Elena Canyon was analyzed. Through 16S rRNA gene sequencing and analysis in QIIME2 and DADA2, a similar composition dominated by Firmicutes and Bacteroidota was observed, suggesting microbial convergence. However, beta diversity showed significant differences (p < 0.05), indicating host-associated divergence. Taken together, these results highlight the importance of integrating ethical approaches, standardized methodologies, and open science under the One Health framework, concluding that the combination of genetics and the microbiome strengthens ecological understanding and the sustainable management of species in arid ecosystems.
Tesis (Maestría en Ciencias en Recursos Naturales y Medio Ambiente en Zonas Áridas)
Keywords: Conservation genetics, fecal microbiome, terrestial mammals, non invasive sampling, One Health.